Studies on The Biology and Control of Chaetocnema Basolis Baly (Chrysomelidae: Coleoptera ) - Doval, S L; Mathur, B P; Kaul, C K (Annals of Arid Zone, 2016)
The pest passed through two generations during a single wheat growing period. Under field conditions the activity of first generation starts in the second half of November and that of the second generation in the last week of January. Thereafler the population undergoes hibernation. DDT + methyl parathion, BHC and carbaryl dusts gave very good results in the control of Chaetocnema basalis Baly, in wheat crop.